2018
DOI: 10.1038/sj.bdj.2018.77
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood incidence rate of paediatric dental extractions under general anaesthetic in South West England

Abstract: Introduction Extraction of decayed teeth is the most common reason for UK children aged 5-9 years to receive a general anaesthetic. Inequalities in oral health are well recognised, but is under-explored in dental general anaesthesia (DGA).Methods Secondary analysis of routinely collected data from three local authorities in South West England was used to assess: 1) dental activities recorded for children <18 years attending NHS general dental practitioners (GDP); 2) the incidence rate of DGA and disease severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Referring dentists request that these children have sedation or even GA, for what is often simple treatment. Due to the escalating concerns about the numbers of children who are undergoing a GA for dental treatment, it is imperative that different approaches are sought for these vulnerable groups [22]. General dental care professionals have a fundamental role in identifying children with dental anxiety and proactively offering simple psychological interventions, before acute treatment needs arise [23].…”
Section: Discussionmentioning
confidence: 99%
“…Referring dentists request that these children have sedation or even GA, for what is often simple treatment. Due to the escalating concerns about the numbers of children who are undergoing a GA for dental treatment, it is imperative that different approaches are sought for these vulnerable groups [22]. General dental care professionals have a fundamental role in identifying children with dental anxiety and proactively offering simple psychological interventions, before acute treatment needs arise [23].…”
Section: Discussionmentioning
confidence: 99%
“…While some local authorities with higher levels of dmft and deprivation also had positive associations between these variables and hospital admissions, these associations are likely more complex, and linked in a multifaceted way to the social determinants of health, as well as other structural, behavioural and health service‐related factors. For example, previous research has shown that while admissions are strongly associated with area deprivation, rates of DGA have remained high in less deprived areas, 14 and more advantaged groups 8 . Additionally, any overall national decreases in caries experience in younger children may be masking increases in inequalities as improvements in oral health are predominantly seen in more affluent groups 14 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research has shown that while admissions are strongly associated with area deprivation, rates of DGA have remained high in less deprived areas, 14 and more advantaged groups 8 . Additionally, any overall national decreases in caries experience in younger children may be masking increases in inequalities as improvements in oral health are predominantly seen in more affluent groups 14 . The complexity of these patterns makes analysis of these clusters challenging, specifically due to the use of aggregate data, and difficulties in drawing causal mechanisms and pathways from these types of data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations